The Implementation Effect of Industrial Work Practices on Student Work Readiness - Risma Niswaty; Hajrah Lestari AM; Sirajuddin Saleh; Aris Baharuddin; Sitti Hardiyanti Aras (Pinisi Business Administration Review, 2019)
Especially vocational education programs must be oriented to the needs of the labor market. Therefore, educational institutions need to establish cooperation with the industrial world. The aims of this study: to find out the implementation of industrial work practices of students. To find out the work readiness of students of class XI competency in Office Administration skills at SMK Negeri 1 Jeneponto. To determine the effect of the implementation of industrial work practices on the work readiness of students of class XI competency in Office Administration expertise at SMK Negeri 1 Jeneponto. The approach used in this study is a quantitative approach to the type of association research There are 3 data collection techniques used in this study, observation, questionnaires and documentation techniques. The data analysis technique used is descriptive analysis and inferential analysis techniques. The results of this study can be summarized as follows: Implementation of Industrial Work Practices of students Competency in Office Administration Skills at SMK Negeri 1 Jeneponto is included in the excellent category. The work readiness of Class XI Office Administration students at SMK Negeri 1 Jeneponto belongs to the very high category. And there is a strong and significant influence between the implementation of industrial work practices on work readiness of students.